El reciclaje como herramienta para la conservación del ambiente y la concienciación de la comunidad educativa de la escuela Héroes de Jambelí de la ciudadela Voluntad de Dios del cantón Machala periodo Lectivo 2013. - Rogel Rogel, Yuli Jacqueline (2013)
Solid waste pollution is something latent that never seems to end up implying deterioration to water, air and soil factors important to the life of the planet. In the Canton Machala produces about 130 tons of garbage per day and suffers from a place to deposit solid waste, they are open garbage dumps, where they have been throwing garbage for many years. Source: Undersecretaries of Environmental Quality, Ministry of the Environment